2018
DOI: 10.1021/acs.jctc.8b00165
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multicenter Density Functional Tight Binding Model for Plutonium Surface Hydriding

Abstract: We detail the creation of a multicenter density functional tight binding (DFTB) model for hydrogen on δ-plutonium, using a framework of new Slater-Koster interaction parameters and a repulsive energy based on the Chebyshev Interaction Model for Efficient Simulation (ChIMES), where two- and three-center atomic interactions are represented by linear combinations of Chebyshev polynomials. We find that our DFTB/ChIMES model yields a total electron density of states for bulk δ-Pu that compares well to that from Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…44,48,[53][54][55][56] It was previously shown that DFTB can recover DFT-level accuracy for systems under reactive conditions through tuning E Rep to DFT computed forces or training sets. [46][47][48]50,[57][58][59][60][61] Hence, most of the generic E Rep interactions in the mio-1-1 parameterization were replaced with force-matched ones (discussed below) that were determined specically for aqueous glycine chemistry. Universal force eld dispersion terms 62 were used for E Disp .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…44,48,[53][54][55][56] It was previously shown that DFTB can recover DFT-level accuracy for systems under reactive conditions through tuning E Rep to DFT computed forces or training sets. [46][47][48]50,[57][58][59][60][61] Hence, most of the generic E Rep interactions in the mio-1-1 parameterization were replaced with force-matched ones (discussed below) that were determined specically for aqueous glycine chemistry. Universal force eld dispersion terms 62 were used for E Disp .…”
Section: Methodsmentioning
confidence: 99%
“…[37][38][39] However, DFT-MD simulations are too computationally intensive to probe beyond picosecond and nanometer time and length scales, whereas chemical equilibrium under these conditions can take nanoseconds or longer to be achieved. [40][41][42] Semi-empirical methods such as the density functional tight binding (DFTB) method [43][44][45][46][47][48] combine approximate quantum mechanics with empirical functions to offer an efficient alternative that is orders of magnitude less computationally intensive while retaining a high degree of accuracy. The computational efficiency of DFTB allows for initiating many independent simulations concurrently to generate trajectories that can approach chemical equilibrium timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Optical properties of natural pigments (flavonols) adsorbed on boron nitride nanotubes were also analyzed using DFTB (Figure 8) [315]. Some DFTB surface adsorption studies have also given rise to reactivity studies, for example water splitting on anatase (001) [316] or H 2 dissociation on plutonium [317].…”
Section: Supported or Embedded Systemsmentioning
confidence: 99%
“…Their influential investigations of molecular hydrogen interaction with δ-Pu are of great significance, as they compared the dissociation barriers with different surfaces and found the most favorable dissociation channel [18,19]. Goldman's innovative calculation provided valuable insight into the H 2 dissociation pathways with an energy map, and also indicated that the dissociation reaction is highly active even at ambient conditions [20,21]. In a thorough study of H 2 interaction with PuO 2 , Yu and Meng compared various adsorption sites to evaluate H 2 dissociation and atomic H diffusion energy barriers.…”
Section: Introductionmentioning
confidence: 99%